Annexes: Core CAADP M&E and supplementary indicators - Badiane, Ousmane; Makombe, Tsitsi (International Food Policy Research Institute, 2015)
This section presents data and trends across three levels of the CAADP Results Framework (AUC and NPCA 2015) as well as supplementary data and trends